CLINICAL, PARACLINICAL CHARACTERISTICS AND BACTERIAL ISOLATION RESULTS IN PATIENTS WITH POSTPARTUM INFECTION AT OBSTETRICS AND GYNECOLOGY DEPARTMENT, HAI PHONG UNIVERSITY HOSPITAL, 2024–2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics, bacterial isolation results, and treatment outcomes in patients with postpartum infections treated at the Department of Obstetrics and Gynecology, Hai Phong University Hospital, during 2024–2025.Subjects and Methods: A descriptive cross-sectional study was conducted on 32 postpartum women diagnosed with postpartum infections and treated at the Department of Obstetrics and Gynecology from 2024 to 2025. Lochial specimens were collected for bacterial isolation and identification.Results: The 25–29-year age group accounted for the highest proportion (46.9%). The rate of postpartum infection was higher in women undergoing cesarean section (62.5%) than in those with vaginal delivery (37.5%). Endometritis was the most common clinical presentation (37.5%). Fever was present in 100% of cases; leukocytosis >10 G/L was observed in 78.1% of patients; and the mean CRP level was 57.3 ± 49.1 mg/L. Escherichia coli was the most frequently isolated pathogen. Overall, 96.9% of patients responded well to treatment and were discharged.Conclusion: Postpartum infections were most commonly observed in women aged 25–29 years and occurred predominantly after cesarean section. Endometritis was the predominant clinical form. Fever, leukocytosis, and elevated CRP levels are useful supportive indicators for diagnosis. Most patients showed a favorable response to treatment.
Keywords: Postpartum infection; bacterial isolation; endometritis.